2004
DOI: 10.1097/01.shk.0000133591.47776.bd
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietin Stimulates Angiogenesis and Healing of Ischemic Skin Wounds

Abstract: Wound healing in ischemic tissues such as flap margins due to inadequate blood supply is still a source of considerable morbidity in surgical practice. Adequate tissue perfusion is particularly important in wound healing. We investigated the effects of recombinant human erythropoietin (rHuEPO) on wound healing in an ischemic skin wound model. Sixty-three Sprague-Dawley rats were used. Normal incisional wound and H-shaped double flaps were used as the wound models. Animals were treated with rHuEPO (400 IU/kg) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 32 publications
(30 reference statements)
2
70
1
3
Order By: Relevance
“…In addition to preserving existing capillaries, EPO has also been shown to accelerate healing in the ischemic flap model by amplifying reparative angiogenesis (10)(11)(12). It is known that in organ injury, such as a rodent myocardial infarction model (31), EPO mobilizes endothelial progenitor cells (CD34 + /flk-1) that subsequently travel via the circulation and migrate into injury sites to drive neoangiogenesis, ultimately reducing tissue hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to preserving existing capillaries, EPO has also been shown to accelerate healing in the ischemic flap model by amplifying reparative angiogenesis (10)(11)(12). It is known that in organ injury, such as a rodent myocardial infarction model (31), EPO mobilizes endothelial progenitor cells (CD34 + /flk-1) that subsequently travel via the circulation and migrate into injury sites to drive neoangiogenesis, ultimately reducing tissue hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Among the pleiotropic effects of EPO reported, a number of investigators have reported significant activity of EPO in promoting the healing of ischemic raised cutaneous skin flaps (10)(11)(12)(13)(14), ischemiareperfusion in random musculocutaneous flaps (15), incisional wounds (10,13), and in colonic anastomoses (16,17). Additionally, skin thermal burns also have been reported to respond in a beneficial way to EPO (18).…”
Section: Introductionmentioning
confidence: 99%
“…EPO is able to trigger healing by increasing angiogenesis, by the formation of granulation tissue, by the production of collagen as well as by re-epithelialisation [9,19,23]. Especially in complicated wounds like burns and under ischemic conditions, EPO seems to promote healing [8,20]. The prior aim was thus to verify whether there is a fundamental cellular response to EPO in vitro, which might serve to explain-at least in part-the healing improvement achieved by the application of EPO in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…Supplying of oxygen and nutrients for collagen synthesis completed in the process of angiogenesis. 46 L. camara Linn. leaf extract ointment 5% more better than 10% for wound healing.…”
Section: Discussionmentioning
confidence: 99%